Feasibility Analysis And Innovation System Of Toraja Coffee Commodities In South Sulawesi, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
Agricultural farming began as a subsistence farming system, then developed into the commercialization of agriculture in line with the extensibility and intensification. South Sulawesi is a potential coffee center, there is 7 coffee center districts with production above two thousand tons, namely Enrekang, North Toraja, Tana Toraja, Luwu, Pinrang, Sinjai, and Gowa Regencies. The research method is a descriptive and explanatory survey in Tana Toraja Regency, South Sulawesi, Indoneisa. The research time is 3 (three) months, from October to December 2022. Data was collected through in-depth interviews, focus discussion groups (FGDs), and field observations on coffee commodity development sites. The data collection process begins with determining the sampling frame of all units of the target population and then determining the respondent units through random selection. The variables analyzed in this study include (a) planting area, area of potential for coffee commodity development; (b) production and productivity; (c) the income achieved by farmers now and in the future; (d) investment, maintenance and operational costs, (e) the number of benefits achieved present and future; (f) a comparison of the costs and benefits achieved; and (h) the rupiah exchange rate against the dollar, as well as tradeable and nontrade able inputs and the efficiency of the DRC value. The results showed that the net income of coffee farmers with the introduction of recommended technology reached Rp. 30,390,000 per hectare, while farmers who still need to apply technology reached Rp. 13,463,000 per hectare. The additional income farmers earn if they apply the recommended technology is 17.3 million or there is an increase in income of 57.5%, which is described as the IBCR value of 4.1. Analysis of NPV, Gross B/C and Net B/C ratio shows that the development of coffee commodities in Tana Toraja Regency is feasible for the next 25 years with average benefits of 2.4 (Gross B/C ratio) and 1.4 (Net B/C ratio). The results of the DRC Analysis show that the DRC value < from the current SER value, while the DRC coefficient value (0.09) is less than 0.5. This shows that the development of Toraja coffee as an export commodity can compete in the international market.